Investigating Factors Influencing Turnover Intention of Nurses at Petrokimia Gresik Hospital: A Qualitative Research using a Case Study Approach - Hartanto, Luky (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Turnover intentions often occur in the world of work, and there are several factors that can trigger turnover intentions, including workload and work stress factors. This research was conducted to determine the workload and work stress factors that influence nurses’ turnover intentions at Petrokimia Gresik Hospital. Data was obtained by interviewing nurses who had worked for more than three years. This research was discussed by describing the results of the interviews and strengthening them with scientific statements and existing theories. This results in the conclusion that workload and work stress are factors that are often found in the emergence of turnover intentions in employees. Meanwhile, salary and work environment factors do not influence the intention to leave the nursing job at the Petrokimia Gresik Hospital.